ANALISIS RASIO KEUANGAN TERHADAP PERUBAHAN LABA PADA PERUSAHAAN FARMASI - Putri Sarirati; Dewi Melani (Aliansi : Jurnal Manajemen dan Bisnis, 2021)
The purpose of this study is to determine the effect of the company's financial ratio empirically, both partially and simultaneously on changes in profit.  The selection of samples was conducted by purposive sampling method from 12 company samples obtained by 9 company samples. The study used data analysis methods with multiple linear regressions and performed classical assumption tests first.The results of this study showed that the Current Ratio variable partially had an influence and negatively on the change in profit. Based on the resultsof the t test witha t count of -3,341 fromthetable's t value of -2,030 and a significance level of 0.002 0.05. The Return on Assets variable partially has an effect and positives on the change in profit. Based on the resultsof the t test with at calculate of 12,978 ofthetable's t value of 2,030 and the significance level of 0.000 0.05. While the Debt to Equity Ratio variable and the Total Assets Turnover variable partially had no significant effect on the change in profit. Simultaneous testing showed that variables Current Ratio, Return On Assets, Debt to Equity Ratio,and Total Assets Turnover simultaneously had a significant effect on changes in profits. Based on the results of the test F with a significance value of 0.000 0.05 and Fcalculated 46.745 from the table Fvalueof 2.61. The variable influence rate of Current Ratio, Return On Assets, Debt to Equity Ratio and Total Assets Turnover simultaneously is 82.4%.